2003
DOI: 10.1046/j.1432-1033.2003.03679.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel binding site for calmodulin in ammodytoxin A, a neurotoxic group IIA phospholipase A2

Abstract: The molecular mechanism of the presynaptic neurotoxicity of snake venom phospholipases A2 (PLA2s) is not yet fully elucidated. Recently, new high‐affinity binding proteins for PLA2 toxins have been discovered, including the important intracellular Ca2+ sensor, calmodulin (CaM). In the present study, the mode of interaction of group IIA PLA2s with the Ca2+‐bound form of CaM was investigated by mutational analysis of ammodytoxin A (AtxA) from the long‐nosed viper (Vipera ammodytes ammodytes). Several residues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
23
1
Order By: Relevance
“…Our structure-function studies of ß-neurotoxic sPLA 2 s (Ivanovski et al, 2000(Ivanovski et al, , 2004Petan et al, 2002Petan et al, , 2005Prijatelj et al, 2000Prijatelj et al, , 2002Prijatelj et al, , 2003Prijatelj et al, , 2006bPrijatelj et al, , 2008Pungerčar et al, 1999) clearly show that different parts of the toxin molecule have separate roles in the distinct steps of the complex mechanism of presynaptic neurotoxicity . Most significantly, by selectively mutating parts of the DPLA 2 molecule, we were able to map the residues that separate the weakly ß-neurotoxic sPLA 2 from the 150-fold more potent AtxA (Prijatelj et al, 2008).…”
Section: Structural Determinants Of Presynaptic Neurotoxicity Of Splamentioning
confidence: 78%
See 3 more Smart Citations
“…Our structure-function studies of ß-neurotoxic sPLA 2 s (Ivanovski et al, 2000(Ivanovski et al, , 2004Petan et al, 2002Petan et al, , 2005Prijatelj et al, 2000Prijatelj et al, , 2002Prijatelj et al, , 2003Prijatelj et al, , 2006bPrijatelj et al, , 2008Pungerčar et al, 1999) clearly show that different parts of the toxin molecule have separate roles in the distinct steps of the complex mechanism of presynaptic neurotoxicity . Most significantly, by selectively mutating parts of the DPLA 2 molecule, we were able to map the residues that separate the weakly ß-neurotoxic sPLA 2 from the 150-fold more potent AtxA (Prijatelj et al, 2008).…”
Section: Structural Determinants Of Presynaptic Neurotoxicity Of Splamentioning
confidence: 78%
“…However, the latter is almost 150-fold more toxic in mice (Prijatelj et al, 2003). To our great surprise, the introduction of the YIRN cluster into DPLA 2 did not increase its toxicity; on the contrary, the DPLA 2 YIRN mutant was more than five times less toxic than DPLA 2 (Prijatelj et al, 2003). Additionally, our study on the importance of the N-terminal residue Phe24, in which it was replaced by other aromatic (tyr or trp), polar uncharged (ser or asn) or hydrophobic (ala) residues, suggested that Phe24 is also involved in the neurotoxicity of Atxs, apparently at a stage not involving enzymatic activity or interactions with the high-affinity binding proteins R25, R180 and CaM (Petan et al, 2002).…”
Section: Structural Determinants Of Presynaptic Neurotoxicity Of Splamentioning
confidence: 99%
See 2 more Smart Citations
“…This region probably is involved in the neurotoxic activity of this PLA 2 . Several studies made with other PLA 2 also showed that C-terminal region play important role for the neurotoxic effect and the difference in the amino acid sequences of this region has a evident relationship to neurotoxic potency (Krizaj, 1989;Curin-Serbec, 1991;Lomonte, 2003;Prijatelj, 2003). Thus these conserved basic amino acid residues seem to be involved in the neurotoxic effect of new crotoxin B isoform PLA 2 F6a from the Crotalus durissus collilineatus but it is not the unique region responsible for this effect.…”
Section: Discussionmentioning
confidence: 99%